2015
DOI: 10.1152/ajpheart.00525.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration accelerates reductions in cerebral blood flow during prolonged exercise in the heat without compromising brain metabolism

Abstract: Reductions in cerebral blood flow and extracranial perfusion, induced by dehydration during prolonged exercise in the heat, may be coupled to fatigue. However, cerebral metabolism remains stable through enhanced O2 and glucose extraction. Thus, fatigue developed during prolonged exercise with dehydration is related to reductions in cerebral blood flow rather than to the cerebral metabolic rate for O2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 50 publications
8
52
0
Order By: Relevance
“…For example, Nybo et al (2002a) reported that CMRO 2 is ß7% higher during 'hyperthermic' exercise when core temperature was ß1.6°C higher than control -suggesting a Q10 of ß1.5. Conversely, Trangmar et al (2014Trangmar et al ( , 2015 reported no change in CMRO 2 during exhaustive exercise, even when core temperature was further elevated as a result of dehydration.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Nybo et al (2002a) reported that CMRO 2 is ß7% higher during 'hyperthermic' exercise when core temperature was ß1.6°C higher than control -suggesting a Q10 of ß1.5. Conversely, Trangmar et al (2014Trangmar et al ( , 2015 reported no change in CMRO 2 during exhaustive exercise, even when core temperature was further elevated as a result of dehydration.…”
Section: Introductionmentioning
confidence: 91%
“…Conversely, Trangmar et al . (, ) reported no change in CMRO 2 during exhaustive exercise, even when core temperature was further elevated as a result of dehydration.…”
Section: Introductionmentioning
confidence: 95%
“…4). Haemoconcentration during heat stress is sometimes interpreted to indicate some level of dehydration, which has been shown to potentiate reductions in CBF and CDO 2 (Trangmar et al 2014(Trangmar et al , 2015. Additionally, the haemoconcentration that occurred with both cooling and heating caused an increase in blood viscosity (Table 1), which would be expected to compromise CBF according to Poiseuille's Law (Nichols et al 1974).…”
Section: Factors Contributing To Cdo 2 During Isolated Thermal Strainmentioning
confidence: 99%
“…Some reports show cognitive impairments with acute and prolonged hypoxia despite global CDO 2 and CMRO 2 being maintained, a conundrum that might be partly explained by regional reductions in CBF that become more pronounced with continued hypoxic exposure (Lawley et al 2017). Severe heat stress causes large decreases in CDO 2 but CMRO 2 is maintained or even increased and cognitive impairments are observed only when the task complexity is maximised (Nybo et al 2002b;Trangmar et al 2015;Piil et al 2017). Whole body cooling decreases both central and peripheral nerve conduction velocity and has been shown to slow central information processing (Rammsayer et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration during exercise is expected, and is directly proportional to exercise intensity, duration, environmental conditions, types of clothes and equipment (24,25,26) . A loss of body mass greater than 2% may negatively affect the cardiovascular system (5,23,30) , immune system (11) , brain function (28,29) , and performance, due to fluid imbalance (24,29) .…”
Section: Introductionmentioning
confidence: 99%